1994
DOI: 10.1002/cne.903460206
|View full text |Cite
|
Sign up to set email alerts
|

Visual system of the fossorial mole‐lemmings, Ellobius talpinus and Ellobius lutescens

Abstract: Ocular regression in subterranean species has been shown to be associated with a number of alterations in the retina and in retinal pathways. In order to examine the consequences of eye reduction, the visual system was studied in two species of the murine genus, Ellobius, a specialized fossorial rodent. The axial length of the eye is only 2.2 mm in E. lutescens and 2.9 mm in E. talpinus. The mean soma size of ganglion cells in Nissl-stained flatmounts is approximately 10 microns in E. lutescens and 12 microns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 136 publications
(197 reference statements)
3
32
0
Order By: Relevance
“…In spite of their fossorial life, light detection may still play an important role in the lives of these 'blind' animals for circadian entrainment or setting seasonal rhythms. Results obtained in some studies in other fossorial vertebrates support this hypothesis [Cooper et al, 1993;Herbin et al, 1994;Crish et al, 2006].…”
Section: Nontelencephalic Secondary Prosencephalon and Hypothalamussupporting
confidence: 72%
“…In spite of their fossorial life, light detection may still play an important role in the lives of these 'blind' animals for circadian entrainment or setting seasonal rhythms. Results obtained in some studies in other fossorial vertebrates support this hypothesis [Cooper et al, 1993;Herbin et al, 1994;Crish et al, 2006].…”
Section: Nontelencephalic Secondary Prosencephalon and Hypothalamussupporting
confidence: 72%
“…In a noncentral region of the barn owl IC, visual stimuli can modulate responses to accompanying auditory stimuli, although they rarely elicit responses independently (Bergan and Knudsen 2009) except with accompanying pharmacological manipulation of the SC (Gutfreund et al 2002). Anatomical studies have revealed multiple visually sensitive regions that project to shell regions of the IC, including connections from visual and parietal cortices (Coleman and Clerici 1987;Cooper and Young 1976;Druga et al 1997), the retina (Herbin et al 1994;Itaya and Van Hoesen 1982;Yamauchi and Yamadori 1982), and the SC (Adams 1980;Coleman and Clerici 1987;Covey et al 1987). Whether such inputs also project to the central nucleus is less clear, but the signals could conceivably reach that region through less direct routes involving connections within the auditory pathway (e.g., Coleman and Clerici 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It is substantial in hamster (Pickard and Silverman, 1981;Johnson et al, 1988;Youngstrom et al, 1991;Elliott et al, 1995;Ling et al, 1998;Muscat et al, 2003) and some primates (Mick et al, 1993). It is also present in blind mole rat and mole-lemming (Herbin et al, 1994) but absent in other fossorial species (Nemec et al, 2004(Nemec et al, , 2008Crish et al, 2006). It is limited to the horizontal limb of the diagonal band of Broca in the mink (Martinet et al, 1992).…”
Section: Basal Telencephalonmentioning
confidence: 94%
“…The ipsilateral input in squirrels is species dependent (Smale et al, 1991;Major et al, 2003). Laterality is also inconsistent among subterranean rodents Herbin et al, 1994;Negroni et al, 2003;Nemec et al, 2004;Crish et al, 2006). The functional impact of these interspecies differences is still unclear (Morin, 2007).…”
Section: Scn and Hypothalamusmentioning
confidence: 94%